First-line nivolumab plus ipilimumab with two cycles of chemotherapy versus chemotherapy alone (four cycles) in metastatic non-small cell lung cancer: CheckMate 9LA 2-year patient-reported outcomes. (April 2023) - Reck, Martin; Ciuleanu, Tudor-Eliade; Cobo, Manuel; Schenker, Michael; Zurawski, Bogdan; Menezes, Juliana; Richardet, Eduardo; Bennouna, Jaafar; Felip, Enriqueta; Juan-Vidal, Oscar; Alexandru, Aurelia; Cheng, Ying; et al.
Abstract: Background: In CheckMate 9LA (NCT03215706), first-line nivolumab plus ipilimumab with chemotherapy (2 cycles) significantly improved overall survival versus chemotherapy (4 cycles) in patients with metastatic non-small cell lung cancer and no known sensitising epidermal growth factor receptor / anaplastic lymphoma kinase alterations. We present exploratory patient-reported outcomes (PROs; minimum follow-up, 2 years). Methods: In patients ( N  = 719) randomised 1:1 to nivolumab plus ipilimumab with chemotherapy or chemotherapy alone, disease-related symptom burden and health-related quality of life were assessed using the Lung Cancer Symptom Scale (LCSS) and 3-level EQ-5D (EQ-5D-3L). Treatment-phase changes in LCSS average symptom burden index (ASBI), LCSS three-item global index (3-IGI) and EQ-5D-3L visual analogue scale (VAS) and utility index (UI) over time were analysed descriptively and using mixed-effect model repeated measures. Time-to-deterioration/improvement analyses were conducted. Results: Treatment-phase PRO questionnaire completion rates were >80%. Mean treatment-phase changes showed no deterioration from baseline in both arms for LCSS ASBI/3-IGI and EQ-5D-3L VAS/UI; however, minimally important differences were not met. Mixed-effect model repeated measures analyses showed overall reduction in symptom burden from baseline for both arms; changes from baseline for LCSS 3-IGI and EQ-5D-3L VAS/UI were numerically improved with nivolumab plus ipilimumab with chemotherapy versus chemotherapy, but minimally important differences were not met. Nivolumab plus ipilimumab with chemotherapy delayed time-to-definitive-deterioration versus chemotherapy (LCSS ASBI: hazard ratio, 0.62 [95% confidence interval, 0.45–0.87]); results were similar across PRO measures. Conclusions: At 2-year minimum follow-up, first-line nivolumab plus ipilimumab with chemotherapy reduced the risk of definitive deterioration in disease-related symptom burden and health-related quality of life versus chemotherapy and maintained QoL in patients with metastatic non-small cell lung cancer. Clinical trial registration: ClinicalTrials.gov Identifier, NCT03215706. Highlights: Patient-reported outcomes were assessed using the Lung Cancer Symptom Scale and EQ-5D in CheckMate 9LA. Risk of symptom deterioration was lower with nivolumab + ipilimumab + chemo versus chemo. 1L nivolumab + ipilimumab + chemo maintained quality of life in patients versus chemo. Data confirm clinical benefit of 1L nivolumab + ipilimumab + chemo in metastatic non-small cell lung cancer.